Hubungan Pengetahuan dengan Perilaku Pencegahan Komplikasi Diabetes Melitus - Hasanah, Yulia (Indonesian Journal of Health Community, 2024)
Diabetes melitus is a group of metabolic disorders characterized by increased blood glucose levels due to defects in insulin secretion, insulin action, or both. If diabetes melitus is not managed or handled properly, it can cause various complications. Prevention of these complications is one of the health behaviors. One of the factors that influences behavior is knowledge. This study aims to determine the relationship between knowledge and behavior to prevent complications of diabetes melitus. This research is a quantitative research with a cross sectional research design. This research was carried out at the Haji Abdoel Madjid Batoe Regional Hospital from 21 June to 24 July 2023. The population in this study were all diabetes melitus patients from January to June 2023, totaling 350 people with a sample of 76 people. using the purposive sampling method, this research was analyzed using univariate and bivariate analysis with the chi square test. The data collection tool uses a questionnaire. The results show that there is a relationship between knowledge and behavior to prevent diabetes melitus complications at Haji Abdoel Madjid Batoe Muara Bulian Hospital, Batanghari Regency with a p-value = 0.001.